Response of hydrodynamic environment to land reclamation in Sanmen Bay, China over the last half-century - Shi, Peijie; Yang, Wankang; Xu, Xuefeng; Zhang, Feng (Frontiers in Marine Science, 2024)
Sanmen Bay (SMB) is one of the important harbors in Zhejiang Province. It is a semi-enclosed shallow bay that has undergone large-scale land reclamation activities. Long-term reclamation has changed the hydrodynamic conditions of SMB, such as tide, residual current, tidal prism, water exchange capacity, and tidal asymmetry. In this study, three typical periods of numerical models, based on historical charts and remote sensing, were established to investigate the influence of reclamation activities on the hydrodynamic conditions of SMB from 1971 to 2020. These model results reveal that the amplitude and phase of M2, the main tidal components in SMB, decreased by ~0.1–0.3 m and ~ 5°–15°, respectively, over the last half-century. Additionally, under the influence of ~200 km2 reclamation, many hydrodynamic conditions in SMB also changed. This includes the reduction of a residual current and tidal prism, an increase in residence time, and a change in tidal asymmetry characteristics. The residence time in nearby Xiayangtu exhibited a downward trend from 2003 to 2020, because land reclamation squeezed, and thus, enhanced the residual current eddy. The water-exchange capacity of the bay became weaker with the reduction of tidal prism to one-third and an increase in residence time. The tidal asymmetry characteristic of SMB changed from half of flood dominant to fully flood dominant by the influence of shoreline and bathymetry, which raised the flood risk. Research on the response of the hydrodynamic environment to reclamation activities in SMB reminds the local government to reassess the impact of land reclamation on the hydrodynamic environment.